Closing the academy–Business gap by building intellectual capital in professional formation - Vélez-Rolón, Adela M.; Pulido López, Alejandra; Méndez-Pinzón, Manuel; Neira-Bermudez, Diego (Frontiers in Sociology, 2023)
Introduction The rapid advances in technology, market pressures, globalization, and, recently, the COVID-19 pandemic show the need to find educational models that respond to these realities while improving the employability levels of young people and promoting economic growth. This research analyzes how the professional formation model, where two learning spaces, the academy, and the company, are combined, promotes the closing of gaps and economic growth, through the development of intellectual capital that arises from this relationship, in an emerging economy such as Colombia. Methods The methodology used corresponds to a qualitative approach, where the vision of the actors involved in the training process at the undergraduate level in Colombia is analyzed through semi-structured interviews, focus groups, and documentary analysis. Results and discussion The results show five major elements to consider for the formation of the intellectual capital required for the success of the relationship and the reduction in the gaps between academia and business: decision-making mechanisms, inter-organizational coordination, knowledge.